Does Agricultural Food Production Reflect the Diversity of Diets in Bauchi, Nigeria?. (14th June 2022) - Sosanya, Mercy; Freeland-Graves, Jeanne; Gbemileke, Ayodele; Shokunbi, Olutayo; Leshi, Oluwatosin; Akinyemi, Oluwaseun; Samuel, Folake
Abstract: Objectives: In Africa, Nigeria has the largest economy and the greatest investment in agriculture. Yet, the country ranks 103 rd of 116 in the Global Hunger Index, and only 23% of children receive diets with the minimum diversity. Inadequate consumption of nutrient-dense foods is an underlying cause of undernutrition. This study qualitatively evaluated the food production and consumption of rural households in Bauchi State, Nigeria. Methods: Data were collected via six focus group discussions with 48 women of child-bearing ages 16–33 years, from farming households in six Local Government Areas (LGAs) in Bauchi State. Discussions were conducted in the Hausa language; audio-recorded, transcribed, translated into English, analyzed and organized into themes. Results: Emerging themes include foods produced and consumed, food processing/preservation methods, foods perceived as nourishing and experiences of hunger. Commonly produced foods included nine starchy staples, seven legumes/oil seeds, 11 vegetables, four types of fruits and eight types of livestock. In three of six LGAs, commonly consumed foods were from only three food groups including starchy staples, legumes and vegetables. Dairy was listed only in two LGAs and meat in one LGA. Husbands reportedly ate good food, including meat outside the home, but such foods were often unavailable for household members. Participants believed that because they are women, and live in villages, one should eat whatever is available. Crops produced for their cash value were often not consumed. Harvested crops were preserved/processed via traditional methods associated with nutrient losses, including sun-drying and winnowing off the outer layers of milled grains. Mothers generally knew what foods were nourishing, but did not provide these for their children because these were sold for financial gain. Widespread food shortages, initially perceived to affect only women, reportedly disrupted household harmony and precipitated visible signs of child malnutrition. Conclusions: A variety of agricultural food products that can contribute to adequate nutrient intakes are produced by rural households in Bauchi State, yet diets are limited in diversity. Thus, urgent strategies are needed to promote dietary diversity, and optimize the food systems for improved nutrition of women and children. Funding Sources: Oxfam LINE Project, Bauchi.